THE IRISH DIASPORA IN CANADA: BRIAN MOORE’S THE LUCK OF GINGER COFFEY - Cruz, Patrícia Lane Gonçalves da (Em Tese, 2010)
In this work, I analyze the theoretical boundaries between the concepts of immigration and diaspora as represented in Brian Moore’s novel  The luck of Ginger Coffey. This novel raises the possibility of discussing different concepts of diaspora and immigration, as well as various aspects,  like the perception of the experience, the fluidity of terms regarding mobility, the criteria that define diaspora and immigration, the concepts of home and homeliness, and assimilation.